Innovation and reform in college-based VET contexts: an outline of research in England and Germany - Ertl, H; Kremer, H (ESRC Centre on Skills, Knowledge and Organisational Performance (SKOPE), 2009)
This paper provides an overview of a research project on the impact of reforms on teaching and learning in college-based VET (vocational education and training) contexts. Using a comparative perspective, the project examines how far VET reforms lead to innovative teaching practice at vocational colleges (Berufsschulen) in Germany and FE (Further Education) colleges in England. The paper provides some background to ongoing reforms of college-based training in the two countries. It also looks at the degree to which administrative and leadership structures at colleges enable and prepare lecturers to embrace changes and how far these structures results in a reactive or proactive stance regarding educational innovation. It is concluded that the comparatively stable situation in German vocational colleges seems to allow lecturers to reflect more freely on innovative practice in general. In contrast, innovative activities of FE college lecturers are often limited to decisions regarding the management of content in teaching a constantly changing portfolio of qualifications offered by their college. This difference has a profound impact on the notions of professionalism expressed by the two groups of lecturers.